2016
DOI: 10.1111/ane.12595
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian experience of the influence of endovascular treatment on headache in patients with ruptured intracranial aneurysms

Abstract: There was a reduction of the primary headache after endovascular treatment of ruptured brain aneurysm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Numerous studies have been conducted to evaluate the headaches associated with endovascular procedures as well as the effects of non-ruptured aneurysms or non-haemorrhagic arteriovenous malformations (AVMs) on headache [2][3][4][5][6]. However, studies evaluating the relationship between DSA and headache have been limited.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been conducted to evaluate the headaches associated with endovascular procedures as well as the effects of non-ruptured aneurysms or non-haemorrhagic arteriovenous malformations (AVMs) on headache [2][3][4][5][6]. However, studies evaluating the relationship between DSA and headache have been limited.…”
Section: Introductionmentioning
confidence: 99%
“…A potential correlation between aneurysms, AVMs and headache is no new concept, and studies have suggested that for patients harboring these vascular anomalies, headache may be more prevalent than in the general population [ 3 , 4 , 12 ]. Based on epidemiological studies of the general Danish population, the lifetime cumulated prevalence for both sexes is 16–18 % for migraine and 78 % for tension-type headache [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests a reduction of post-treatment mortality and morbidity with the transition from open surgery to EVT [ 1 ]; however, functional outcomes such as headache after EVT have received only little attention. These vascular lesions may predispose to headache in their own right [ 2 , 3 ], and several studies describe headache as a presenting symptom of both conditions [ 4 , 5 ]. What is less known, is how this headache is affected by endovascular treatment procedures, and the expected time frame of headache resolution.…”
Section: Introductionmentioning
confidence: 99%